Reinterpretasi Makna Adil Dalam Al-Qur’an Menggunakan Pendekatan Ma’na Cum Maghza - Haliza, Nurul; Lubis, Nuraini; Pratama, Yoga (Kartika: Jurnal Studi Keislaman, 2024)
Studies on justice in the Qur'an have so far been carried out through linguistic and normative approaches, but have not fully explored the main message (maghza) of the verses contextually. This article aims to reinterpret the meaning of justice in the QS. An-Nisa (4): 58 using a ma'na cum maghza hermeneutical approach. This research is library research using qualitative methods, using primary sources in the form of the Koran and classical to contemporary tafsir books, as well as secondary sources in the form of relevant scientific books and articles. The analysis was carried out in three stages, namely exploring al-ma'na al-tarikhi (historical significance), al-maghza al-tarikhi (historical significance), and al-maghza al-mutaharrik (dynamic significance). The research results show that at the al-ma'na al-tarikhi level, QS. An-Nisa (4): 58 emphasizes that justice is a moral and legal obligation that must be enforced objectively, without being influenced by personal interests, tiesemotional, and power relations. Power and authority are not a privilege, but a mandate that must be accounted for morally and socially. The dynamic significance of this verse can be used for law enforcement and social justice in the contemporary context.